Towards AI-enhanced ballet learning - Trajkova, M. (Proceedings of the 6th International Conference on Movement and Computing, 2019)
Since its codified genesis in the 18th century, ballet training has largely been unchanged: it relies on the word of mouth expertise passed down generation to generation and in tools that do not adequately support both dancers and teachers. Moreover, top-tier training is only found in a few locations around the world and comes at an exceptional price. In this context, artificial intelligence (AI)-based video tools might represent an affordable and non-invasive alternative: it would allow dancers and teachers to self-assess as well as enable skilled dance teachers to connect with a wider audience. In my research, I study how to design and evaluate AI-based tools to improve ballet performance for dancers and teachers.